-(8y+1)-(-7y-3)=2

Simple and best practice solution for -(8y+1)-(-7y-3)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(8y+1)-(-7y-3)=2 equation:


Simplifying
-1(8y + 1) + -1(-7y + -3) = 2

Reorder the terms:
-1(1 + 8y) + -1(-7y + -3) = 2
(1 * -1 + 8y * -1) + -1(-7y + -3) = 2
(-1 + -8y) + -1(-7y + -3) = 2

Reorder the terms:
-1 + -8y + -1(-3 + -7y) = 2
-1 + -8y + (-3 * -1 + -7y * -1) = 2
-1 + -8y + (3 + 7y) = 2

Reorder the terms:
-1 + 3 + -8y + 7y = 2

Combine like terms: -1 + 3 = 2
2 + -8y + 7y = 2

Combine like terms: -8y + 7y = -1y
2 + -1y = 2

Add '-2' to each side of the equation.
2 + -2 + -1y = 2 + -2

Combine like terms: 2 + -2 = 0
0 + -1y = 2 + -2
-1y = 2 + -2

Combine like terms: 2 + -2 = 0
-1y = 0

Solving
-1y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '-1'.
y = 0

Simplifying
y = 0

See similar equations:

| 15-29=2(x-3) | | 7+s^2(t+4-5r)= | | 5a+8+(-2)=-7 | | -(8y+1)-(-7y-3)=3 | | -(6y+4)-(-5y-6)=5 | | 100(z+3)-3(z-1)=4(z-3)+(z-1) | | y=2(-3) | | 11x=9x+6 | | 3x+10=8x-7 | | b=2f+8 | | 3(-3y+8)=-(-9y+120) | | 4m+18+4m=-20-42-2m | | 35(x+6)=35x-10 | | 1=5x+2 | | 17x+2y=3 | | 12=5m-21 | | 7p=-24p | | =-0.45 | | 4x+3-7=-5 | | 6-5x-27=4 | | x=(-4.9)(t^2)+8.9886t+2.15 | | 4x+3-7=5+-5 | | 6x-10y=-1 | | 2.5m+35= | | 2x^3-28x^2+48x=0 | | 57+12=7m+149 | | 3/x=18/30 | | x+-5=7 | | log(6x-8)=1-logx | | 4x+1/3=1 | | 7n+8=26-2n | | x/50=3/25 |

Equations solver categories